Testing the Intervention of OER Renewable Assignments in a College Course - Maimoona Humaid Al Abri; Nada Dabbagh (Open Praxis, 2019)
The purpose of this study was to explore students and instructor perceptions of the concept of renewable assignments in the open educational resources (OER) movement. Mixed methods were used, with a combination of a survey and semi-structured interview, administered at George Mason University in the United States. Eleven graduate students enrolled in the Instructional Design and Technology program in the course Advanced Instructional Design were invited to complete an online survey. A face-to-face interview was conducted with the instructor of the course. Descriptive statistics and thematic analysis were used to examine the results of the study. The data analysis found that only a small number of students were knowledgeable about OER, but the majority of participants indicated that they were very satisfied with the concept of renewable assignments. The findings suggest further investigation of the pedagogical models that tend to support student-generated OER.